The Landscape of Local Authority in Sierra Leone : How "Traditional" and "Modern" Justice and Governance Systems Interact - Manning, Ryann Elizabeth (World Bank, Washington, DC, 2014)
The topic of this paper is, in the words of one reviewer, 'one of the most discussed sociological and societal issues in African studies: the relationship between traditional institutions and new institutions'. Often in such discussions, the 'traditional' and 'modern' are framed as if in opposition to one another, and debate centers on whether and to what extent tradition should cede to modernity, or modernity should yield to the dictates of traditional norms. In Sierra Leone, much has been said and written about the abuses of the chieftaincy system and customary law, including the history of chieftaincy as a tool for colonial rule, the exploitation of youth labor, the exclusion of 'strangers' and young men from weak lineages from access to land or marriage, the imposition of harsh and arbitrary fines, and discriminatory practices against women. Many have argued that abusive and autocratic practices by traditional authorities helped to fuel the civil war that ravaged Sierra Leone in the 1990s by driving aggrieved young men away from their villages and into the various armed factions, in rebellion against a social system that trapped them in a rural underclass. On the other hand, many people see the traditional justice and governance systems as important mechanisms for maintaining peace and social order, particularly in rural areas. Some on this side of the argument see the war as having resulted from a breakdown in this social order, and make the case for strengthening the chieftaincy systems to consolidate peace and promote development today.